Aitor Boada Benito (ed.), Safo, Madrid: Ediciones Torremozas, 2020, 199 págs. ISBN: 978-84-7839-815-7 - López-Maroto Quiñones, Sara (Cuadernos de Filología Clásica. Estudios griegos e indoeuropeos, 2021)
Reseña de la obra de Aitor Boada Benito (ed.), Safo, Madrid: Ediciones Torremozas, 2020, 199 págs. ISBN: 978-84-7839-815-7